Quantifying the bearing surface wear of retrieved hip replacements. Issue 1 (17th February 2019) - Bergiers, Sean; Hothi, Harry; Richards, Robin; Henckel, Johann; Hart, Alister
Abstract : Accurate quantification of bearing material loss from retrieved metal‐on‐metal (MOM) hip replacements is key to understanding their failure. Geometric methods are currently the only means of estimating volumetric wear from retrieved implants and numerous contrasting approaches to obtain these measures have been published. Data collection strategies have been thoroughly discussed and refined to minimise the effect of error incurring factors; however, there is an opportunity to optimise the current methods of estimating the pre‐wear geometry and, therefore, improve the accuracy of wear volume measurements. An automated analysis strategy to quantify volumetric wear is proposed in this study, which utilises the entire bearing surface to determine the implants pristine geometry. This involves the iterative removal of geometrically effected data points to optimise the fit and size of a perfect sphere. Once fitted, this reference geometry is compared with the measured data, in its entirety, to calculate the volume change representative of the quantity of material lost. Improving the reliability of this parameter could influence the care of a million patients that remain with MOM hip implants. Rigorous validation of this method will dominate future work, ensuring that the accuracy and reliability of this approach are sufficient to provide clinically meaningful data.